SOS in the mangrove ecosystem of Nazabal Beach in Encrucijada, Villa Clara, Cuba - García, José Javier Carrazana; Bacallao, Damaris Olivera; García, Rafael Armiñana; Pérez, George Argota; Castro, Oriali Fraga; Duarte, Rigoberto Fimia (Journal of Marine Studies, 2025)
Climate change is an irrefutable reality that constitutes today, and in the future, one of the main threats affecting the survival of life on planet Earth. The objective of the research was to introduce the scientific result, social project: Monitoring the mangrove. The research was actually carried out in the village of Nazabal, Encrucijada, in the province of Villa Clara, Cuba. Fifteen students of the group of the twelfth-grade number 1 of the Urban Pre-University Institute "Miguel de la Guardia" participated in it. For the development of the research work, methods of information collection and processing of the collected information were used, as well as statistical and mathematical methods. It was found that students have little knowledge in relation to the mangrove ecosystem. The research enabled the students to develop actions that contributed to mitigate this problem. These were conceived in close relationship with the territorial delegation of the Ministry of Technology and Environment of Cuba. It was possible to verify during the research the dumping of solid waste in the mangrove roots, mangrove felling, dumping of debris and construction materials on the coastline, among others. The actions carried out in the study area made it possible to systematize concepts and skills of an ecological and protectionist nature and complied with the Action Plan for the implementation of the State Plan to Confront Climate Change. In order to mitigate the difficulties detected, a social project was introduced, which was evaluated by experts.